ANALISIS KESENIAN TERBANG GENJRING PADA TRADISI CUKUR RAMBUT BAYI DI KAMPUNG KALAPA DUA DESA MARGALUYU KECAMATAN MANONJAYA - Ita Faoziah; Asep Wasta; Asti Triestari (Prodi Pendidikan Sendratasik FKIP UMTAS, 2021)
This research entitled “The art of flaying genjring on the tradition of baby hair shaving in Kalapa Dua village, Margaluyu village, Manonjaya district”. Genjring flaying art is a traditional art using a tambourine musical instrument. Genjring flaying art is often used in celebrations, thanksgiving, entertainment at the opening of the event, in the tradition of shaving babies as well as the spread of Islam. Member of this genjring flying art is an elderly person. This study aims to analyze the form of presentation, and the inheritance of the art of flying genjring in Kalapa Dua village, Margaluyu village, Manonjaya District. The method used in this research is a qualitative method with a descriptive analytic approach. Data collection techniques through, observation, interviews, documentation and literature study.